Care - Wer sorgt für wen? - Moser, Vera; Pinhard, Inga (Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft, 2010)
Against the background of the necessity of (old) care - keyword: demographic change - and the changes in the area of child care, many questions arise regarding generational and gender arrangements. The authors examine the central questions with a view to fields of practice: All-day school, child care, care of the elderly - and do not spare the problem of the shadow economy: mainly women, often with a migration background, who work illegally in care in German households.